Standardized methodology for calculating the cost of medical care funded by government sources - M. A. Sdvizhkova; S. A. Kovaleva; D. V. Fedyaev; V. V. Omelyanovskiy (Фармакоэкономика, 2025)
Background. Current challenges in healthcare include an increase in life expectancy and in medical care (MC) needs, thereby putting pressure on the limited resources of the Russian healthcare system. Efficient allocation of financial resources is becoming a priority. Calculating the cost of MC is considered as a key tool that affects the efficiency of the system. However, the existing calculation methods remain fragmented, which reduces their transparency and limits their application. The need for the unification of approaches to ensure standardization, improve the quality, and increase the accessibility of MC underscores the relevance of the present study.Objective: to develop a standardized methodology for calculating the cost of MC funded by government sources, aimed at enhancing transparency, standardizing calculations, and supporting a versatile approach in healthcare management.Material and methods. The study was based on the analysis of regulatory documentation for calculations in the public healthcare sector. The study methodology involved information search techniques, expert surveys, statistical data processing, and economic analysis.Results. The analysis of existing calculation methodologies revealed their fragmentation, disparities in the level of detail, methods for determining costs, and specific interpretations. The developed standardized methodology included the categorization of costs into direct and indirect, as well as the use of both normative and actual data. The cost of medical services and MC cases were considered the primary calculation units. The methodology was adapted to accommodate various funding sources and regional characteristics.Conclusion. The suggested methodology enhances the transparency, detail, and consistency of calculations, thereby facilitating effective management of resources within the healthcare system. Flexibility of the approaches allows for further adaptation to meet the needs of different stakeholders within the system.